Case I: when the lift is at rest:
Applying Newton’s 2nd law of motion on the hanging body, we get
Spring force + gravitational force = 0
Or, -kx + mg = 0 or, kx = m*9.8 or, 49 = 9.8*m
Or, m = 49/9.8 = 5kg
(i) When the lift is moving downward:
Applying Newton’s 2nd law of motion on the hanging body, we get
mg – kx = ma or, 49 – kx = 5*5
or, kx = 49-25 = 24N
(ii) When the lift is moving downward:
Applying Newton’s 2nd law of motion on the hanging body, we get
kx-mg = ma or, kx – 49 = 5*5
or, kx = 25+49 = 74N
(iii) When lift moves with constant velocity:
Here, acceleration, a = 0
Applying Newton’s 2nd law of motion on the hanging body, we get
mg – kx = m*a or, 49 – kx= 0
or, kx = 49N